Sulfide electrolyte membrane, preparation method thereof and solid-state battery
By adopting a multi -layered sulfide electrolyte film, the combination of ultra -thin nano tablets and micron particles is used to solve the problem of the growth of lithium branches crystal in the process of charging and discharge of vulcanizes, improve the critical current density of the battery and anti -branched crystal crystal. Ability to enhance the safety and cycle performance of the battery.
Patent Information
- Application Number
- CN202411637291.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-15
AI Technical Summary
During the charging and discharging process, sulfide electrolytes are prone to problems of lithium dendrites growing along the grain boundaries, resulting in rapid short-circuiting of the battery and reducing cycling performance.
Multi-layered sulfide electrolyte film, including sulfide inaxides with a thickness of <400nm, and micron particles with 1-30 μm with 1-30 μm. The first electrolyte layer of the cloth.
Improve the critical current density of vulcanic electrolytes and the ability to resist lithium branches, enhance the safety and circulation performance of the battery, and reduce the interface impedance between layers and layers.
Smart Images

Figure CN119381534A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid-state batteries, and in particular to a sulfide electrolyte membrane and a preparation method thereof, and a solid-state battery. Background Art
[0002] Solid electrolyte membrane is a key component of solid-state batteries, and sulfide solid electrolytes have attracted much attention due to their excellent ion transport performance. Sulfide electrolytes can be densely packed through simple cold pressing and exhibit ion conductivity comparable to that of liquid electrolytes. This makes sulfide electrolytes an important material for improving battery performance, especially in terms of high energy density and safety, showing broad application prospects.
[0003] However, in practical applications, sulfide electrolytes are prone to the problem of lithium dendrites growing along the grain boundaries during the charge and discharge process. This not only causes the battery to short-circuit quickly, but also significantly reduces the cycle performance of all-solid-state batteries. To solve this problem, researchers have proposed a variety of modification schemes, including adding an organic layer or an oxide inorganic layer to the surface of the sulfide electrolyte membrane to enhance the electrolyte membrane's anti-dendrite ability. However, these methods introduce new substances and interface layers, resulting in poor compatibility between the layers and poor stability of the two-phase interface. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the embodiments of the present application includes providing a sulfide electrolyte membrane and a preparation method thereof, and a solid-state battery to improve the critical current density and anti-lithium dendrite ability of the sulfide electrolyte membrane, and the stability and compatibility between layers are good.
[0005] In the first aspect, an embodiment of the present application provides a sulfide electrolyte membrane, comprising a first electrolyte layer, a second electrolyte layer and a first electrolyte layer arranged in sequence; the first electrolyte layer comprises a plurality of sulfide inorganic electrolyte nanosheets, the second electrolyte layer comprises a plurality of sulfide inorganic electrolyte micron particles, the sulfide inorganic electrolyte in the nanosheets has the same chemical composition as the sulfide inorganic electrolyte in the micron particles; the thickness of each nanosheet is less than 400 nm, and the thickness of the first electrolyte layer is ≥1 μm.
[0006] On the one hand, the present application uses nanosheets with a thickness of less than 400nm. This ultra-thin nanosheet has a higher critical current density than traditional electrolyte particles, and the two-dimensional structure of the nanosheet enables lithium ions to disperse current more effectively when migrating on its surface, thereby reducing local current density and reducing the possibility of dendrite formation; further, by using a multilayer structure of a composite of nanosheet layers and particle layers, the lithium ion transmission efficiency can be effectively improved. Moreover, the two-dimensional characteristics of the nanosheets on both sides of the electrolyte membrane make lithium dendrites more inclined to precipitate on the surface parallel to the pole piece, rather than in the direction perpendicular to the pole piece. This feature not only reduces the threat of dendrite growth to the battery, but also improves the anti-dendrite ability of the entire membrane, enhancing the safety and cycle performance of the battery. On the other hand, the nanosheets of the present application are consistent with the materials of the sulfide inorganic electrolyte in the micron particles, and the contact interface of the same material reduces the space charge layer formed by the potential difference between different materials, thereby reducing the interface resistance and improving the migration efficiency of ions, so that the battery can still maintain good performance at high currents.
[0007] In some embodiments of the present application, the sulfide inorganic electrolyte includes Li7P3S 11 、Li3PS4、Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li6PS5Cl and Li 7-x PS 6-x Cl x Any one of .
[0008] In some embodiments of the present application, the D 50 1-30μm.
[0009] The D 50 Limiting the size to the range of 1-30μm can not only improve the ionic conductivity and stability of the membrane structure, but also effectively reduce the risk of lithium dendrite growth and enhance the adaptability and economy of the material.
[0010] In some embodiments of the present application, the thickness of the second electrolyte layer is 10-300 μm.
[0011] Limiting the thickness of the second electrolyte layer to 10-300μm helps improve the overall ionic conductivity of the battery and the charge and discharge efficiency. It also makes the electrolyte membrane less prone to cracking during the charge and discharge process, enhancing the stability and service life of the battery. Moreover, within this thickness range, the electrolyte layer can provide sufficient space for lithium ion migration while reducing the concentration of local current density. This effectively reduces the risk of lithium dendrite growth and improves battery safety.
[0012] In some embodiments of the present application, the thickness of the first electrolyte layer is 1-5 μm.
[0013] Limiting the thickness of the first electrolyte layer to the range of 1-5μm can reduce the diffusion path of lithium ions in the electrolyte, thereby improving ionic conductivity. It also helps to improve battery efficiency, reduce energy loss, and enhance battery cycle performance. Within the thickness range of 1-5μm, the electrolyte layer can effectively control the current density and reduce local current concentration. This helps to inhibit the formation of lithium dendrites, reduce the risk of short circuits, and enhance battery safety.
[0014] In the second aspect, an embodiment of the present application provides a method for preparing the above-mentioned sulfide electrolyte membrane, comprising: mixing and dissolving sulfide inorganic electrolyte nanosheets, a binder and a solvent to obtain a first slurry; mixing and dissolving sulfide inorganic electrolyte micron particles, a binder and a solvent to obtain a second slurry; applying the first slurry on a carrier, drying, to obtain a first electrolyte layer; applying the second slurry on the first electrolyte layer, drying, to obtain a second electrolyte layer formed on the surface of the first electrolyte layer; applying the first slurry on the second electrolyte layer, drying, and rolling to obtain a sulfide electrolyte membrane; wherein the drying is carried out under an inert protective atmosphere, or under dew point conditions of -50°C.
[0015] The preparation method adopts multi-layer coating technology to form a first electrolyte layer, a second electrolyte layer and a first electrolyte layer coated again. At the same time, the combination of nanosheets and micron particles can effectively inhibit the growth of lithium dendrites while ensuring the efficiency of lithium ion transmission, thereby improving the safety and cycle performance of the battery.
[0016] In some embodiments of the present application, the binder includes any one of hydrogenated styrene-butadiene block copolymer, styrene-butadiene rubber, polyisobutylene, butadiene rubber and polytetrafluoroethylene.
[0017] The use of binders such as hydrogenated styrene-butadiene block copolymer, styrene-butadiene rubber, polyisobutylene, butadiene rubber and polytetrafluoroethylene can not only improve the adhesion performance and mechanical strength of the electrolyte membrane, but also enhance the thermal stability and chemical resistance, and provide good processability and adaptability.
[0018] In some embodiments of the present application, in the first slurry, the mass ratio of the binder to the sulfide inorganic electrolyte nanosheets is (1-15):(99-85).
[0019] Limiting the mass ratio of binder to sulfide inorganic electrolyte nanosheets within the range of (1-15):(99-85) can not only enhance the adhesion and mechanical strength of the membrane, but also optimize ionic conductivity, improve processability, promote battery performance balance, reduce costs, and improve long-term stability.
[0020] In some embodiments of the present application, in the second slurry, the mass ratio of the binder to the sulfide inorganic electrolyte microparticles is (1-15):(99-85).
[0021] Limiting the mass ratio of binder to sulfide inorganic electrolyte microparticles within the range of (1-15):(99-85) can not only improve the mechanical strength and ionic conductivity of the membrane, but also optimize the slurry fluidity, improve the uniformity and moisture resistance of the membrane, and reduce production costs.
[0022] In some embodiments of the present application, the solvent in the first slurry and the solvent in the second slurry each independently include any one of toluene, xylene, heptane, octane and isobutyl ether.
[0023] These solvents have good solubility and can dissolve various types of polymers and binders without deteriorating the sulfide electrolyte. For example, toluene and xylene are commonly used organic solvents that can effectively dissolve binders such as hydrogenated styrene-butadiene block copolymer to form a uniform slurry.
[0024] In some embodiments of the present application, in the first slurry, the mass fraction of the sulfide inorganic electrolyte nanosheets in the solvent is 35-80%.
[0025] In some embodiments of the present application, in the second slurry, the mass fraction of the sulfide inorganic electrolyte microparticles in the solvent is 35-80%.
[0026] Limiting the mass fraction of sulfide inorganic electrolyte nanosheets and micron particles in the solvent to 35-80% can not only improve the fluidity of the slurry and the uniformity of the membrane, but also optimize the ionic conductivity, enhance the mechanical strength of the membrane, improve drying efficiency, reduce costs and environmental friendliness.
[0027] In some embodiments of the present application, the inert protective atmosphere includes nitrogen or argon.
[0028] In some embodiments of the present application, the drying temperature is 90-150° C., and the drying time is 2-10 h.
[0029] Limiting the drying temperature to 90-150°C and the drying time to 2-10 hours can effectively volatilize the solvent and shorten the drying time. It can also improve the drying efficiency and the density and chemical stability of the membrane, reduce residual solvents, optimize battery performance and reduce costs.
[0030] In a third aspect, an embodiment of the present application provides a solid-state battery comprising any of the above-mentioned sulfide electrolyte membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a schematic diagram of the structure of the sulfide electrolyte membrane provided in Example 1 of the present application.
[0033] Icons: 1-second electrolyte layer; 2-first electrolyte layer; 3-sulfide inorganic electrolyte nanosheets; 4-sulfide inorganic electrolyte microparticles. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0035] An embodiment of the present application provides a sulfide electrolyte membrane, comprising a first electrolyte layer, a second electrolyte layer and a first electrolyte layer arranged in sequence; the first electrolyte layer comprises a plurality of sulfide inorganic electrolyte nanosheets, the second electrolyte layer comprises a plurality of sulfide inorganic electrolyte micron particles, the sulfide inorganic electrolyte in the nanosheets has the same chemical composition as the sulfide inorganic electrolyte in the micron particles; the thickness of each nanosheet is less than 400 nm, and the thickness of the first electrolyte layer is ≥1 μm.
[0036] The design of the sulfide electrolyte membrane of the present application enables it to have a higher critical current density, which can effectively inhibit the growth of lithium dendrites, thereby reducing the risk of short circuit. Specifically, the ultra-thin nanosheets (thickness <400nm) used in the sulfide electrolyte membrane provided by the present application have a higher critical current density than traditional electrolyte particles. This is because the two-dimensional structure of the ultra-thin nanosheet enables lithium ions to disperse the current more effectively when migrating on its surface, thereby reducing the local current density and reducing the possibility of dendrite formation; further, by using a multilayer structure of a composite of nanosheet layers and particle layers, the lithium ion transmission efficiency can be effectively improved. Moreover, the two-dimensional characteristics of the nanosheet make lithium dendrites more inclined to precipitate on the surface parallel to the pole piece, rather than in the direction perpendicular to the pole piece. This feature not only reduces the threat of dendrite growth to the battery, but also improves the anti-dendrite ability of the entire membrane, and enhances the safety and cycle performance of the battery. In addition, since the materials of the nanosheet and the sulfide inorganic electrolyte in the micron particles are consistent, the interface bonding is tighter, the interface resistance is reduced, and the migration efficiency of the ions is improved, so that the battery can still maintain good performance at high currents.
[0037] By way of example, the thickness of each nanosheet includes, but is not limited to, 50 nm, 70 nm, 90 nm, 100 nm, 120 nm, 150 nm, 200 nm, 240 nm, 300 nm, 350 nm, 380 nm, and 400 nm.
[0038] As an example, the thickness of the first electrolyte layer includes but is not limited to 1.4μm, 1.8μm, 2μm, 2.5μm, 3μm, 3.4μm, 3.8μm, 4μm, 4.3μm, 4.6μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 9μm, and 10μm.
[0039] In the embodiment of the present application, the sulfide inorganic electrolyte includes Li7P3S 11 、Li3PS4、Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li6PS5Cl and Li 7-x PS 6-x Cl x Any one of .
[0040] In the present application, the D 501-30 μm, and the thickness of the second electrolyte layer is 10-300 μm. As an example, the D 50 Including but not limited to 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, and 30μm. As an example, the thickness of the second electrolyte layer includes but is not limited to 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm, 300μm.
[0041] Micronized particles D 50 In the range of 1-30μm, the specific surface area of the particles can be increased, thereby improving the ion conduction path. This helps to improve the overall ionic conductivity of the electrolyte, promote the rapid migration of lithium ions, and thus improve the charge and discharge efficiency of the battery. 50 Smaller than 1 μm will result in lower ionic conductivity of the membrane, and may also cause the failure to effectively isolate the positive and negative electrodes during battery assembly, resulting in a short circuit. 50 If the particle size is greater than 30μm, the thickness of the entire electrolyte membrane cannot be reduced, and the energy density of the battery may also decrease. Within this particle size range, the particles can form a dense and uniform membrane structure. This structure helps to reduce interface defects and porosity, improve the mechanical strength and stability of the membrane, and thus enhance the cycle performance of the battery. Particles within this particle size range can form a more uniform electric field distribution in the electrolyte membrane and reduce the concentration of local current density. This helps to inhibit the growth of lithium dendrites, reduce the risk of short circuits, and improve the safety of the battery.
[0042] The thickness of the second electrolyte layer is limited to the range of 10-300μm, which can reduce the ion diffusion barrier while maintaining sufficient ion conduction path; this helps to improve the overall ion conductivity of the battery and improve the charging and discharging efficiency. The electrolyte layer within this thickness range usually has good mechanical strength and toughness. This makes the electrolyte membrane less prone to cracking during the charging and discharging process, enhancing the stability and service life of the battery. It can also make good contact between the electrolyte layer and the electrode, reduce the interface impedance, help improve the electrochemical performance of the battery, and reduce energy loss. In addition, within this thickness range, the electrolyte layer can provide sufficient space for lithium ion migration while reducing the concentration of local current density; this can effectively reduce the risk of lithium dendrite growth and improve the safety of the battery.
[0043] The following is an explanation of a method for preparing a sulfide electrolyte membrane provided in an embodiment of the present application.
[0044] A method for preparing a sulfide electrolyte membrane, comprising:
[0045] Step S1: adding sulfide inorganic electrolyte nanosheets and a binder into a solvent according to corresponding mass ratios, stirring and dissolving them to obtain a first slurry.
[0046] Step S2: adding sulfide inorganic electrolyte particles and a binder into a solvent in a corresponding mass ratio, stirring and dissolving them to obtain a second slurry.
[0047] Step S3: Apply the first slurry obtained in step S1 on the carrier, and dry it under an inert protective atmosphere (N2 or Ar) to obtain a first electrolyte layer; apply the second slurry on the first electrolyte layer, and dry it under an inert protective atmosphere (N2 or Ar) to obtain a second electrolyte layer formed on the surface of the first electrolyte layer.
[0048] In the present application, the carrier is aluminum foil or an organic release film.
[0049] Step S4: Apply the first slurry obtained in step S1 onto the second electrolyte layer obtained in step S3, dry it under an inert protective atmosphere (N2 or Ar), and roll the composite sheet layer into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0050] The preparation method adopts a multilayer coating technology to form a first electrolyte layer, a second electrolyte layer and a first electrolyte layer coated again. The multilayer structure can optimize the ion conduction path, improve the interface contact and reduce the impedance. The different thickness and material properties of each layer can effectively adjust the performance of the overall membrane and provide better ion conductivity and mechanical strength. The use of the same sulfide electrolyte material (nanosheets and micron particles) helps to improve the bonding between layers. The consistency of the materials reduces the interfacial potential difference and interface defects caused by different materials, thereby reducing the interface impedance and improving the migration efficiency of ions. At the same time, the combination of nanosheets and micron particles can improve the mechanical stability of the membrane while maintaining good conductivity. The high specific surface area of sulfide nanosheets helps to provide more reaction interfaces and enhance ion conduction, while sulfide particles provide the necessary structural strength.
[0051] The drying can also be carried out at a dew point of -50°C. Drying is carried out under an inert protective atmosphere or at a dew point of -50°C, which can effectively prevent the influence of moisture and oxygen. The protective atmosphere prevents the adsorption and oxidation reaction of moisture, thereby maintaining the chemical stability of the electrolyte, improving the overall performance of the membrane, and reducing the risk of lithium dendrite formation.
[0052] In the embodiments of the present application, the binder includes but is not limited to hydrogenated styrene-butadiene block copolymer (SEBS), styrene-butadiene rubber (SBR), polyisobutylene (PIB), butadiene rubber (BR) and polytetrafluoroethylene (PTFE).
[0053] In the first slurry, the mass ratio of the sulfide inorganic electrolyte nanosheet to the binder is (99-85): (1-15). As an example, the mass ratio of the sulfide inorganic electrolyte nanosheet to the binder includes but is not limited to 99: 1, 98: 2, 97: 3, 96: 4, 95: 5, 94: 6, 93: 7, 92: 8, 91: 9, 9: 1, 89: 11, 88: 12, 87: 13, 86: 14, 85: 15. The mass ratio of the sulfide inorganic electrolyte nanosheet to the binder is limited to (99-85): (1-15) to fill the tiny gaps in the electrolyte membrane, provide stronger interfacial bonding force, reduce interfacial impedance, and thus improve battery performance. The binder can enhance the toughness of the membrane, so that the membrane cracks or peels off due to stress concentration during charging and discharging, thereby improving the integrity and long-term stability of the membrane.
[0054] In the second slurry, the mass ratio of the sulfide inorganic electrolyte micron particles to the binder is (99-85): (1-15). As an example, the mass ratio of the sulfide inorganic electrolyte micron particles to the binder includes but is not limited to 99: 1, 98: 2, 97: 3, 96: 4, 95: 5, 94: 6, 93: 7, 92: 8, 91: 9, 9: 1, 89: 11, 88: 12, 87: 13, 86: 14, 85: 15. Limiting the mass ratio of the sulfide inorganic electrolyte micron particles to the binder to (99-85): (1-15) helps to improve the uniformity and consistency of the film, can effectively prevent the penetration of water, improve the stability of the film, and avoid performance degradation in a humid environment.
[0055] In the embodiments of the present application, the solvent in the first slurry and the solvent in the second slurry independently include, but are not limited to, toluene, xylene, heptane, octane and isobutyl ether. The mass fraction of the sulfide inorganic electrolyte nanosheets in the solvent is 35-80%. As an example, in the first slurry, the mass fraction of the sulfide inorganic electrolyte nanosheets in the solvent includes but is not limited to 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, and 80%. In the second slurry, the mass fraction of the sulfide inorganic electrolyte micron particles in the solvent is 35-80%. As an example, the mass fraction of the sulfide inorganic electrolyte micron particles in the solvent includes but is not limited to 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, and 80%.
[0056] In the embodiment of the present application, the drying temperature is 90-150°C, and the drying time is 2-10h. As an example, the drying temperature includes but is not limited to 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C. The drying time includes but is not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h.
[0057] Limiting the drying temperature to 90-150°C and the drying time to 2-10 hours can effectively volatilize the solvent and shorten the drying time. Within this temperature range, the interaction and bonding between materials can be promoted, making the membrane more compact after drying, reducing porosity and improving the mechanical strength of the membrane; it also helps to minimize the residual solvent content inside the membrane.
[0058] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0059] Example 1
[0060] Figure 1 This is a schematic diagram of the structure of the sulfide electrolyte membrane provided in Example 1 of the present application, please refer to Figure 1 .
[0061] This embodiment provides a sulfide electrolyte membrane, and the preparation method thereof is as follows:
[0062] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0063] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0064] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0065] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0066] Example 2
[0067] This embodiment provides a sulfide electrolyte membrane, and the preparation method thereof is as follows:
[0068] (1) Li6PS5Cl nanosheets with a thickness of 300 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0069] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0070] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0071] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0072] Example 3
[0073] This embodiment provides a sulfide electrolyte membrane, and the preparation method thereof is as follows:
[0074] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0075] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0076] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 2 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0077] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 2 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0078] Example 4
[0079] This embodiment provides a sulfide electrolyte membrane, and the preparation method thereof is as follows:
[0080] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0081] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0082] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 7 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0083] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 7 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0084] Example 5
[0085] This embodiment provides a sulfide electrolyte membrane, and the preparation method thereof is as follows:
[0086] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0087] (2) D 50 Li6PS5Cl particles with a size of 10 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve, thereby obtaining a second slurry.
[0088] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0089] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0090] Example 6
[0091] This embodiment provides a sulfide electrolyte membrane, and the preparation method thereof is as follows:
[0092] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0093] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0094] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 60 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0095] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0096] Example 7
[0097] This embodiment is basically the same as Embodiment 1, except that the thickness of the second electrolyte layer is 5 μm.
[0098] The preparation method is as follows:
[0099] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0100] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0101] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 5 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0102] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0103] Example 8
[0104] This embodiment is basically the same as Embodiment 1, except that the thickness of the second electrolyte layer is 350 μm.
[0105] The preparation method is as follows:
[0106] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0107] (2) D 50Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0108] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 350 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0109] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0110] Comparative Example 1
[0111] This comparative example is basically the same as Example 1, except that only the second slurry is used for coating on the aluminum foil, and the coating thickness is the total coating thickness of Example 1.
[0112] The preparation method is as follows:
[0113] (1) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a slurry.
[0114] (2) The slurry obtained in step (1) was coated on an aluminum foil with a coating thickness of 28 μm, and dried under N2 (100° C., 4 h) to obtain a sulfide electrolyte membrane.
[0115] Comparative Example 2
[0116] This comparative example is substantially the same as Example 1, except that the thickness of the first electrolyte layer is 0.5 μm.
[0117] The preparation method is as follows:
[0118] (1) Li6PS5Cl nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0119] (2) D 50Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0120] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 0.5 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0121] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 0.5 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0122] Comparative Example 3
[0123] This comparative example is basically the same as Example 1, except that Li6PS5Cl is replaced by the halide electrolyte LiInCl3.
[0124] The preparation method is as follows:
[0125] (1) LiInCl3 nanosheets with a thickness of 100 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0126] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0127] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0128] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0129] Comparative Example 4
[0130] This comparative example is basically the same as Example 1, except that the thickness of each Li6PS5Cl nanosheet is 500 nm.
[0131] The preparation method is as follows:
[0132] (1) Li6PS5Cl nanosheets with a thickness of 500 nm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a first slurry.
[0133] (2) D 50 Li6PS5Cl particles with a size of 3 μm and SEBS were added to xylene in a mass ratio of 98:2 and stirred for 10 h to dissolve to obtain a second slurry.
[0134] (3) The first slurry obtained in step (1) is coated on aluminum foil, the coating thickness is controlled to be 4 μm, and it is dried under N2 (100°C, 4 h) to obtain a first electrolyte layer (sulfide inorganic electrolyte nanosheet layer); the second slurry obtained in step (2) is coated on the first electrolyte layer, the coating thickness is controlled to be 20 μm, and it is dried under N2 (100°C, 4 h) to obtain a second electrolyte layer (sulfide inorganic electrolyte nanosheet layer + sulfide inorganic electrolyte particle layer) formed on the surface of the first electrolyte layer.
[0135] (4) The first slurry obtained in step (1) is coated on the second electrolyte layer obtained in step (3), and the coating thickness is controlled to be 4 μm. The mixture is dried under N2 (100° C., 4 h), and the composite sheet is rolled into a dense film using a rolling device to obtain a sulfide electrolyte membrane.
[0136] The key parameters in the above Examples 1-8 and Comparative Examples 1-4 are detailed in Table 1.
[0137] Table 1
[0138]
[0139] Test example
[0140] In this test example, the sulfide electrolyte membranes prepared in the above examples 1-7 and comparative examples 1-4 were subjected to performance tests, including critical current density, interface impedance, ionic conductivity and the number of cycles (0.1C / 0.1C) at which the capacity retention rate was 80%.
[0141] 1. The critical current density of the battery can be used to evaluate the ability of solid electrolytes to inhibit lithium dendrites. It is defined as the current density that enables lithium dendrites to grow through SEI and SSE and short-circuit the battery. The test method is: use a punch to punch out an electrolyte membrane with a diameter of 10 mm, place lithium metal sheets on both sides of it, and then load it into a mold battery to make a symmetrical lithium battery. Use the Blue Electric Battery Test System to test its critical current density. Set the current size from 0.2mA to 20mA, and continuously increase the current size until the battery fails. The test results are shown in Table 2:
[0142] 2. The sulfide electrolyte membranes prepared in the above Examples 1-7 and Comparative Examples 1-4 were assembled into all-solid-state batteries, and the interface impedance was tested using an impedance tester, and a 0.1C / 0.1C charge and discharge test was performed using a blue battery test system, and the number of cycles at which the capacity decayed to 80% of the initial capacity was recorded. The formula of the positive electrode of the all-solid-state battery is: NCM622 positive electrode material: Li6PS5Cl: nitrile rubber: acetylene black = 70:26:2:2, the negative electrode uses a lithium metal negative electrode, and the operating pressure of the mold battery is 20MPa.
[0143] 3. Ionic conductivity test method: Take an electrolyte membrane disc with a diameter of 10mm and measure its thickness h and area S. Use two clean and flat stainless steel discs with a diameter of 12mm as current collectors, clamp the electrolyte membrane disc, and then install it into the mold battery. Using the LAND battery test system, set the mold battery pressure to 30MPa, the test bias to 10mV, the scanning frequency range to 100KHz~7MHz, test its AC impedance spectrum at 25℃, and read the AC impedance R. According to the formula ionic conductivity σ=h / (S*R), calculate the ionic conductivity of the electrolyte membrane.
[0144] The test results are shown in Table 2:
[0145] Table 2
[0146]
[0147]
[0148] As can be seen from Table 2, the sulfide electrolyte membrane provided by the present application can significantly improve the critical current density of the lithium battery. It can be seen from Example 1, Example 2 and Comparative Example 4 that as the thickness of the nanosheet increases, the critical current density of the electrolyte membrane decreases. It can be inferred that due to the two-dimensional characteristics of the ultra-thin nanosheet, the crystal surface area exposed in the direction parallel to the pole piece is larger, and the lithium dendrites precipitated from the interface are more inclined to precipitate on the surface parallel to the pole piece, rather than precipitate in the direction perpendicular to the pole piece. At the same time, thanks to the short path of the ultra-thin nanosheet in the thickness direction, the number of nanosheets required to precipitate dendrites for short circuit increases with the decrease in thickness, thereby improving the anti-dendrite short circuit resistance of the entire membrane. Moreover, it can be seen from all embodiments and Comparative Example 1 that the interface impedance of Comparative Example 1 is significantly increased. Therefore, the all-solid-state battery prepared using the sulfide electrolyte membrane provided by the present application has a lower impedance, because the sulfide nanosheets and sulfide particles are the same substance, and there is no space charge layer generated by the potential difference at the interface between the two.
[0149] By comparing Comparative Example 2 and Example 4, it can be seen that when the thickness range of the first electrolyte layer is 1-5μm, it is more conducive to improving the critical current density of the lithium battery. When the thickness of the first electrolyte layer is less than 1μm, it will lead to weak anti-dendrite ability and limited improvement in critical current density; when the thickness is greater than 5μm, it will cause higher manufacturing costs and lower battery energy density.
[0150] It can be seen from Example 1, Example 7 and Example 8 that a smaller thickness of the second electrolyte layer will lead to a decrease in the conductivity and critical current density of the membrane, and a larger thickness of the second electrolyte layer will have little effect on the overall conductivity, but the critical current density will be reduced. This is because the granular electrolyte has a higher ionic conductivity and a lower critical current density than the ultra-thin nanosheet electrolyte. The granular electrolyte needs to pass through fewer interfaces during the transmission process, so the ionic conductivity is higher. However, since it cannot induce directional deposition of lithium like ultra-thin nanosheets, the critical current density is smaller and the anti-dendrite ability is worse.
[0151] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A sulfide electrolyte membrane, characterized in that: It comprises a first electrolyte layer, a second electrolyte layer and a first electrolyte layer which are arranged in sequence; the first electrolyte layer comprises a plurality of sulfide inorganic electrolyte nanosheets, the second electrolyte layer comprises a plurality of sulfide inorganic electrolyte micron particles, the sulfide inorganic electrolyte in the nanosheets has the same chemical composition as the sulfide inorganic electrolyte in the micron particles; the thickness of each nanosheet is less than 400nm, and the thickness of the first electrolyte layer is ≥1μm.
2. The sulfide electrolyte membrane according to claim 1, characterized in that The sulfide inorganic electrolyte includes Li7P3S 11 、Li3PS4、Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li6PS5Cl and Li 7- x PS 6-x Cl x Any one of .
3. The sulfide electrolyte membrane according to claim 1, characterized in that The D of the micron particles 50 1-30μm.
4. The sulfide electrolyte membrane according to claim 3, characterized in that The thickness of the second electrolyte layer is 10-300 μm.
5. The sulfide electrolyte membrane according to any one of claims 1 to 4, characterized in that The thickness of the first electrolyte layer is 1-5 μm.
6. A method for preparing a sulfide electrolyte membrane according to any one of claims 1 to 5, characterized in that: include: Mixing and dissolving the sulfide inorganic electrolyte nanosheets, a binder and a solvent to obtain a first slurry; Mixing and dissolving the sulfide inorganic electrolyte micron particles, a binder and a solvent to obtain a second slurry; The first slurry is applied on a carrier and dried to obtain the first electrolyte layer; the second slurry is applied on the first electrolyte layer and dried to obtain the second electrolyte layer formed on the surface of the first electrolyte layer; the first slurry is applied on the second electrolyte layer, dried, and rolled to obtain the sulfide electrolyte membrane; Wherein, the drying is carried out under an inert protective atmosphere or under a dew point condition of -50°C.
7. The preparation method according to claim 6, characterized in that: The binder in the first slurry and the binder in the second slurry each independently include any one of hydrogenated styrene-butadiene block copolymer, styrene-butadiene rubber, polyisobutylene, butadiene rubber and polytetrafluoroethylene; Optionally, in the first slurry, the mass ratio of the binder to the sulfide inorganic electrolyte nanosheets is (1-15):(99-85); Optionally, in the second slurry, the mass ratio of the binder to the sulfide inorganic electrolyte microparticles is (1-15):(99-85).
8. The preparation method according to claim 6, characterized in that: The solvent in the first slurry and the solvent in the second slurry each independently include any one of toluene, xylene, heptane, octane and isobutyl ether; Optionally, in the first slurry, the mass fraction of the sulfide inorganic electrolyte nanosheets in the solvent is 35-80%; Optionally, in the second slurry, the mass fraction of the sulfide inorganic electrolyte microparticles in the solvent is 35-80%.
9. The preparation method according to claim 1, characterized in that: The inert protective atmosphere includes nitrogen or argon; Optionally, the drying temperature is 90-150° C., and the drying time is 2-10 h.
10. A solid-state battery, characterized in that: The invention comprises the sulfide electrolyte membrane according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method and application of thin layered solid electrolyte membrane
CN113851697A
All-solid battery
JP2016143614A
Braking system for hybrid tracked vehicle and control method thereof
KR1020260058485A
High energy-density lithium-sulfur battery and method for making the same
US20240113388A1